2021
DOI: 10.3389/fneur.2020.596871
|View full text |Cite
|
Sign up to set email alerts
|

A Sharp Decline in Burden of Stroke in Rural China During COVID-19 Pandemic

Abstract: This study aimed to explore trends in the burden from stroke associated with home quarantine during the COVID-19 pandemic. Patients with a first-ever stroke registered between January 1 and April 20 from 2010 to 2020 were included in this study. We compared the incidence and the rates of mortality, hospitalization, and diagnosis by neuroimaging for first-ever stroke among a low-income population in rural China during the study periods. Overall, 377 first-ever stroke patients were analyzed in this study period;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Another previous hospital study showed that the odds of stroke was 0.25 times less likely in patients with COVID-19 in comparison with noninfected individuals during SARS-CoV-2 outbreak in New York State [ 38 ]. At a population level, a nationwide Danish study obtained an increased risk of stroke of more than ten times related to a recent diagnosis of COVID-19 [ 9 ], but a Chinese population-based prospective cohort study showed a decrease in the community incidence of ischemic stroke [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another previous hospital study showed that the odds of stroke was 0.25 times less likely in patients with COVID-19 in comparison with noninfected individuals during SARS-CoV-2 outbreak in New York State [ 38 ]. At a population level, a nationwide Danish study obtained an increased risk of stroke of more than ten times related to a recent diagnosis of COVID-19 [ 9 ], but a Chinese population-based prospective cohort study showed a decrease in the community incidence of ischemic stroke [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…Another previous hospital study showed that the odds of stroke was 0.25 times less likely in patients with COVID-19 in comparison with noninfected individuals during SARS-CoV-2 outbreak in New York State [38]. At a population level, a nationwide Danish study obtained an increased risk of stroke of more than ten times related to a recent diagnosis of COVID-19 [9], but a Chinese populationbased prospective cohort study showed a decrease in the community incidence of ischemic stroke [39]. Interestingly, incidence of IHIS in our study was also increased among non-COVID-19 inpatients admitted during the SARS-CoV-2 outbreak, although adjusted estimation of the IRR for the 20NCC compared to the HNCC was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Among six studies that reported increased NCDs mortality, four were conducted in China, with the range of increase between 6.6 and 26% 12 , 16 , 19 , 21 ; one study reported in Philippines that increased by 6% compared to pre-COVID period 13 ; one study reported in Japan that increased by 27% compared to pre-COVID period. 20 Among four studies that reported decreased mortality, with the range of decrease between 1.6% and 11.9% 14 , 15 , 17 , 18 ; two studies reported in China, 17 , 18 one study reported in Japan 15 and one was in Singapore. 14 …”
Section: Covid-19 Effects On Ncds Mortalitymentioning
confidence: 99%
“…Studies reported in-hospital mortality were found across four countries in the WPR, including China, Philippines, Japan and Singapore ( Table 1 ). Of a total of 10 included studies, eight studies reported on cardiovascular mortality, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 one on cancer mortality 20 and one on mental health mortality. 21 Six studies reported increased mortality, 12 , 13 , 16 , 19 , 20 , 21 whereas four studies reported decreased in-hospital or after-hospital mortality.…”
Section: Covid-19 Effects On Ncds Mortalitymentioning
confidence: 99%
See 1 more Smart Citation